PENGEMBANGAN KEGIATAN EKOWISATA DI TAMAN NASIONAL WAY KAMBAS PROVINSI LAMPUNG (Studi Kasus : Pusat Konservasi Gajah) - Gumilang, Heradz; Nitibaskara, Tb. Unu; Rusli, Abdul Rahman (Jurnal Nusa Sylva, 2013)
This activity aims to determine the potential of the potential of tourism resources in National Park of Way Kambas which can be used as an eco-tourism development, visitor perceptions of the existing ecotourism activities in elephant conservation center TNWK, and strategic program development activities in TNWK elephant conservation center. The research activities carried out at National Park of Way Kambas (TNWK) elephant conservation center precisely, Lampung province about a month in June and ending in July 2011 and consists of data collected from primary and secondary data potential tourism resources, perceptions of managers and community participation, characteristics and perceptions of visitor motivation, developing ecotourism activities. Data analysis was done qualitatively and quantitatively. Tourism resources including Sumatran elephant, facilities and infrastructure and supporting facilities are visitor centers, shelters, mosques, bins, lighting, main roads, parking lots, restrooms, and tourist stalls. Based upon existing tourism resources and interviews with managers, the community and visitors, most managers say agree if developed an ecotourism activity involves the local community. In an interview conducted through questionnaires to the visitors, most visitors are interested in tourist activities. Therefore it can be prepared a development strategy in the ecotourism activities TNWK through SWOT analysis with a combination of strength factor and opportunity factor, weakness factor and opportunity factor.